Comparison of Different Labeling Techniques for the LC-MS Profiling of Human Milk Oligosaccharides - Lang, Yinzhi; Zhang, Yongzhen; Wang, Chen; Huang, Limei; Liu, Xiaoxiao; Song, Ni; Li, Guoyun; Yu, Guangli (Frontiers in Chemistry, 2021)
Human milk oligosaccharides (HMOs) exhibit various biological activities for infants, such as serving as prebiotics, blocking pathogens and aiding in brain development. HMOs are a complex mixture of hetero-oligosaccharides that are generally highly branched, containing multiple structural isomers and no intrinsic chromophores, presenting a challenge to both their resolution and quantitative detection. While liquid chromatography-mass spectrometry (LC-MS) has become the primary strategy for analysis of various compounds, the very polar and chromophore-free properties of native glycans hinder their separation in LC and ionization in MS. Various labeling approaches have been developed to achieve separation of glycans with higher resolution and greater sensitivity of detection. Here we compared five commonly used labeling techniques (by 2-aminobenzamide (2-AB), 2-aminopyridine (2-AP), 2-aminobenzoic acid (2-AA), 2,6-diaminopyridine (DAP) and 1-phenyl-3-methyl-5-pyrazolone (PMP)) for analyzing HMOs specifically under hydrophilic-interaction chromatography - mass spectrometry (HILIC-MS) condition. The 2-AA labeling showed the most consistent deprotonated molecular ions, the enhanced sensitivity with the least structural selectivity, as well as the sequencing-informative tandem MS fragmentation spectra for the widest-range of HMOs, therefore this labeling technique was selected for further optimization under the porous graphitized carbon chromatography-mass spectrometry (PGC-MS) condition. The combination strategy of 2-AA labeling and PGC-MS techniques provided online decontamination (removal of excess 2-AA, salts and lactose) and resolute detection of many HMOs, enabling us to characterize the profiles of complicated HMOs mixtures comprehensively in a simple protocol.